The application of a ‘story-telling’ framework to investigative interviews for suspected child sexual abuse - Westcott, Helen L. (Legal and criminological psychology, 2004)
Purpose. This study investigated the usefulness of a ‘story-telling’ approach to understanding investigative interviews with children suspected of being sexually abused. Method. An innovative framework for understanding children's allegations of sexual abuse was devised from the ‘story-telling’ literature, which examined the degree to which essential elements of a story, as well as order or disorder of narrative, were present in accounts of alleged abuse. Other features of the interview, such as the presence of free narrative, reliance on specific questions to elicit an account and bizarre or ‘off-topic’ responses from the child, were also recorded. Transcripts of 70 interviews with children aged up to 12 years, from England and Wales, were coded using a scheme devised specifically for the purpose of the study. Results. The results suggest that although, superficially, the accounts adhered to a story structure, they were often incomplete, ambiguous and disordered to a degree which would impact on understanding. Reliance on specific questions, and other digressionary or non verbal responses from the child also compounded difficulties. Age differences in responding were noted, with the youngest children responding differently from their older peers. Conclusions. Implications for practice include the importance of careful questioning and the value of a second interviewer monitoring the interview. The story-telling framework was a useful tool in suggesting where difficulties may arise for the child in presenting his/her account, and for an observer (e.g. juror) in making sense of the child's experience as elicited in the interview.